The social construction of domestic space in the Brezhnev era - Smolyak, O (2023)
This thesis examines the historical grounds and constitutive elements of the Soviet public discourse on women’s roles in the 1960s-1980s, and how this discourse was reflected and realised in private, or family, communication. Taking as a starting point discussions on the decrease in the birth rate and the availability of leisure time for women, I analyse the insights of newly produced knowledge: how social sciences participated in the construction of public discourse, to what extent policymakers engaged with social sciences research, and what the impact was of new knowledge in communication between the media and a wider, largely female, audience.